2017
DOI: 10.4103/ijmm.ijmm_16_427
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Mechanisms of Antimicrobial Resistance in Staphylococcus Species: A Multicentre Report of the Indian Council of Medical Research Antimicrobial Resistance Surveillance Network

Abstract: There were localised differences in the prevalence of resistance between the centres. The efficacy of the anti-MRSA antimicrobials was very high; however, almost all these antimicrobials showed evidence of creeping MIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 36 publications
5
23
3
Order By: Relevance
“…The ICMR-AMRSN study reported S. aureus to be the most frequently isolated organism in SSTI patients (73.7%). [823] Similarly, our study also showed similar results with S. aureus isolates to be 61.2% in SSTI patients. Further, we also report a high prevalence of S. aureus (35.1%) in BSI patients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The ICMR-AMRSN study reported S. aureus to be the most frequently isolated organism in SSTI patients (73.7%). [823] Similarly, our study also showed similar results with S. aureus isolates to be 61.2% in SSTI patients. Further, we also report a high prevalence of S. aureus (35.1%) in BSI patients.…”
Section: Discussionsupporting
confidence: 85%
“…[20] In India too, Gram-positive infections, particularly MRSA, have been reported to increase exponentially from 29% in 2009 to 47% in 2014. [21] The overall MRSA prevalence in our study was 29.7%, which was lower than the recently reported prevalence of 37.3% by ICMR-AMRSN[8] and 40% as reported by INSAR study. [22] Furthermore, the prevalence varies among different centers across India ranging from 20.2% in Gujarat to 80.4% in Odisha.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Data on the prevalence of MRSA is not uniform. Literature has documented a significant variation in the prevalence rate from different parts of India and between countries [1][2][3][4][5][6][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Studies from India report MRSA prevalence ranging from 6.9% to 87% 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1960s, Methicillin Resistant S.aureus (MRSA) emerged as a potential pathogen causing nosocomial colonization, several outbreaks and difficult-to-treat infections like bacteremia, infective endocarditis, osteoarticular and pleuropulmonary infections. They also causes device related infections like central line associated blood stream infections, ventilator associated pneumonia and catheter associated urinary tract infections [1][2][3][4][5] . It always remains a challenge for physicians to treat and control MRSA infections.…”
Section: Introductionmentioning
confidence: 99%